Uncover the underlying mechanisms of topology and structural hierarchy in energy absorption performances of bamboo-inspired tubular honeycomb. (April 2022) - Zhang, Wen; Yu, T.X.; Xu, Jun
Abstract: Inspired by the microstructures of the bamboo culm wall, we propose a topological tubular honeycomb with structural hierarchy and subsequently demonstrate the outstanding energy absorption capabilities through experiments and numerical modeling. A theoretical model is developed and demonstrated to capture the fundamental structure-performance characteristics of the topology and structural hierarchy in bamboo-inspired tubular honeycombs. The energy absorption capacities of tubular honeycombs with different topological parameters and hierarchical orders are accurately predicted. Results reveal that the governing laws of the structural hierarchy, topological parameters, and their coupling effects on the energy performance of tubular honeycombs. Mechanism maps are also presented to offer insights for designing the next-generation energy absorbers and novel hierarchical/topological structures for energy absorption and impact resistance. Graphical abstract: Highlights: A bamboo-inspired topological honeycomb with a structural hierarchy is proposed. Superior energy absorption capacity and crushing resistance are achieved. An upper-bound analysis is applied to uncover the underlying quantitative laws. The structure-performance characteristics of topology and hierarchy are captured. Mechanism maps are given to offer insights for designing novel energy absorbers.